Robert Morris : From Mnemosyne to Clio : The Mirror to the Labyrinth (1998 - 1999 - 2000). - Musée d'Art Contemporain, Lyon (Milan : Skira editore, 2000)
The Robert Morris retrospective at the Centre Georges Pompidou in 1995 was not able to show Everything of the mobile, deliberately, contradictory work, in constant mutation, of this American artist. It is true that at the end of the 1990s, the French public was already far from totally ignorant of Morris's career, but the theoretician of Minimal Art and inventor of the Antiform still masked the existence of the inveterate experimenter. The Musée d'Art Contemporain has decided to do something about this incomplete perception of Robert Morris's work, by handing over to him an entire floor of the museum each summer for three years running (1998, 1999, 2000). This has allowed him to do what, to his eyes, is more important still than the coherence of his past work, namely to Continue to work.
Robert Morris : From Mnemosyne to Clio : The Mirror to the Labyrinth (1998 - 1999 - 2000), Musée d'Art Contemporain, Lyon, 2000
biog., ind. tent. p. 260-265
Engels
Frans
boek
Keywords: Morris, Robert